East Timor Refugee Nationalism: Adaptation and Identity Conflict in Kupang, 1998-2014 - Teodorikus Hanpalam; Yety Rochwulaningsih; Wasino; Singgih Tri Sulistiyono; Fitri Amalia Shinta Siwi (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2026)
Abstract: This study examines the dynamics of nationalism among former East Timorese refugees in Kupang, East Nusa Tenggara, during 1998–2014. It explores how socio-economic adaptation, identity conflict, and negotiations of belonging unfolded in the aftermath of the 1999 referendum and within the wider context of post-Reformasi Indonesia. Employing a historical method with an interdisciplinary perspective, this research draws on government archives, international reports, newspapers, and in-depth interviews with former refugees, community leaders, government officials, and NGO activists. The analysis is informed by social identity theory, Anderson’s concept of imagined communities, diaspora theory, ethnic boundary-making, and refugee labeling. The findings indicate that refugee nationalism was neither fixed nor singular, but fluid, situational, and continuously renegotiated. Adaptation developed through informal economic strategies, kinship networks, intermarriage, religious participation, and everyday interaction with local communities. At the same time, identity conflict persisted through stigmatization as “refugees” or “new residents,” insecure access to land and public services, unresolved trauma, and fragmented state policies. The study identifies three interrelated forms of nationalism: historical-ideological nationalism, survival nationalism, and hybrid nationalism, particularly among younger generations. These findings reveal the ambivalent character of Indonesian nationalism, which simultaneously articulates inclusion and reproduces exclusion. This study contributes to refugee and nationalism studies by highlighting how marginalized communities negotiate belonging in everyday life and by underlining the need for more inclusive and sustainable integration policies. Abstrak: Penelitian ini mengkaji dinamika nasionalisme mantan pengungsi Timor Timur di Kupang, Nusa Tenggara Timur, pada periode 1998–2014. Kajian ini berfokus pada bagaimana adaptasi sosial-ekonomi, konflik identitas, dan negosiasi rasa memiliki terhadap bangsa berlangsung pascareferendum 1999 dalam konteks Indonesia pascareformasi. Penelitian menggunakan metode sejarah dengan perspektif interdisipliner, melalui pemanfaatan arsip pemerintah, laporan lembaga internasional, surat kabar, serta wawancara mendalam dengan mantan pengungsi, tokoh masyarakat, aparat pemerintah, dan aktivis LSM. Analisis didasarkan pada teori identitas sosial, konsep imagined communities dari Anderson, teori diaspora, pembentukan batas etnis, dan pelabelan pengungsi. Temuan penelitian menunjukkan bahwa nasionalisme para mantan pengungsi tidak bersifat tunggal maupun tetap, melainkan cair, situasional, dan terus dinegosiasikan. Adaptasi berlangsung melalui strategi ekonomi informal, jaringan kekerabatan, perkawinan campuran, partisipasi keagamaan, serta interaksi sehari-hari dengan masyarakat lokal. Namun demikian, konflik identitas tetap bertahan melalui stigmatisasi sebagai “pengungsi” atau “warga baru,” keterbatasan akses terhadap tanah dan layanan publik, trauma yang belum sepenuhnya pulih, serta kebijakan negara yang terfragmentasi. Penelitian ini mengidentifikasi tiga bentuk nasionalisme yang saling berkelindan, yaitu nasionalisme historis-ideologis, nasionalisme survival, dan nasionalisme hibrid, terutama pada generasi muda. Temuan ini menegaskan ambivalensi nasionalisme Indonesia yang di satu sisi menjanjikan inklusi, tetapi di sisi lain masih mereproduksi eksklusi.